The participation of Latin American bodies in the IASB: An update and increased role - Lopes, A. I. (XVI Encuentro AECA "Recuperación económica: confianza e inversión en Europa", 2014)
Accounting in Latin American countries has potential to become an important topic for research. These countries, integrated in emergent economies, have been increasing an important role in the global economy. The main objective of this paper is to put in evidence the role, efforts and influence of multiple standard-settings and supervisory entities from Latin American countries (LATAM) on the IASB’ standards making process, with a particular emphasis in 2010 onwards. The results show that the increased participation of LATAM countries in an international context is important for understand the high degree of convergence of local standards to international accounting standards.